Online46: Online cognitive assessments in elderly cohorts—The British 1946 birth cohort case study - Ziyuan Cai; Valentina Giunchiglia; Rebecca Street; Martina Del Giovane; Kirsty Lu; Maria Popham; Andrew Wong; Heidi Murray‐Smith; Marcus Richards; Sebastian Crutch; Peter J. Hellyer; Jonathan M. Schott; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract INTRODUCTION Online assessments are scalable and cost effective for detecting cognitive changes, especially in elderly cohorts with limited mobility and higher vulnerability to neurological conditions. However, determining the uptake, adherence, and usability of these assessments in older adults, who may have less experience with mobile devices, is crucial. METHODS A total of 1776 members (aged 77) of the Medical Research Council National Survey of Health and Development (NSHD) were invited to complete 13 online cognitive tasks. Adherence was measured through task compliance, while uptake (consent, attempt, completion) was linked to health and sociodemographic factors. Usability was evaluated through qualitative feedback. RESULTS This study's consent (56.9%), attempt (80.5%), and completion (88.8%) rates are comparable to supervised NSHD substudies. Significant predictors of uptake included education, sex, handedness, cognitive scores, weight, smoking, alcohol consumption, and disease burden. DISCUSSION With key recommendations followed, online cognitive assessments are feasible, with good adherence and usability in older adults. Highlights Online cognitive tasks have good uptake, adherence, and usability in older adults. Education, previous cognitive scores, and alcohol consumption predict consent. Alcohol consumption and weight are related to attempting an assessment. Sex, smoking, and disease burden are associated with completion. Protocol challenges and recommendations are identified through qualitative analysis.